2006
DOI: 10.4314/bcse.v20i2.21160
|View full text |Cite
|
Sign up to set email alerts
|

<b>Spectrophotometric and electrochemical studies of the interaction of cryptand 222 with DDQ and I<sub>2</sub> in ethanol solution</b>

Abstract: Spectrophotometric and electrochemical studies concerning the interaction of cryptand 222 with DDQ and I 2 have been performed in ethanol solution. In the case of DDQ, the results are indicative of the formation of C222 + and DDQthrough an equilibrium reaction. The results of I 2 indicate the formation of I 2-ethanol complex and I 3 in the absence of C222. In the presence of C222, the formation of C222I + and I 3 through a non-equilibrium reaction is confirmed. The equilibrium constant of the redox reaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The λ max of one of the CT bands, i.e., 584 nm for the complex in ANCHCl 3 and 587 nm in ANDCM, was chosen for quantitative measurements to provide the highest sensitivity. The radical anion of DDQ, which is intensely purple-colored, was produced in the studied solvents systems as a result of complete charge transfer from the donor (AMFP) to the acceptor (DDQ), as suggested in Scheme 1 [ 36 , 37 ]. This situation appears to be caused by the strong e-donating nature of AMFP, and the high electron affinity of DDQ (1.9 eV) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The λ max of one of the CT bands, i.e., 584 nm for the complex in ANCHCl 3 and 587 nm in ANDCM, was chosen for quantitative measurements to provide the highest sensitivity. The radical anion of DDQ, which is intensely purple-colored, was produced in the studied solvents systems as a result of complete charge transfer from the donor (AMFP) to the acceptor (DDQ), as suggested in Scheme 1 [ 36 , 37 ]. This situation appears to be caused by the strong e-donating nature of AMFP, and the high electron affinity of DDQ (1.9 eV) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that depending on the mole ratio an inclusion complex of the type [1.I + ]I À or [1.I + ]I 3 À is possible, and the UV-vis spectra associated with every chemical specie have been characterized. [14][15][16][17] The UV-vis spectrum of a freshly prepared I 2 /I À solution exhibits three absorbance maxima at 353, 287 and 230 nm (see ESI †) which upon addition of a 50 ppm solution of 1 did not present obvious changes due to the formation of a new chemical specie, moreover the resulting spectrum presented a general saturation in different wavelengths even aer several dilutions.…”
Section: Resultsmentioning
confidence: 99%
“…The average values of both K CT and e calculated at the three wavelengths (447, 542 and 589 nm) were 5089 ± 180 L mol À1 and 3032 ± 96 L mol À1 cm À1 , respectively. The high value of electron affinity of DDQ [13], the high donating power of DMP (from the presence of two electronegative nitrogen atoms, two methyl groups and the ring p system) beside the high dielectric constant of acetonitrile are presumably responsible for the high value of stability constant of the complex. Furthermore, a good evidence of complex stability is confirming from the constant absorbance of Donor Acceptor CT complex …”
Section: Stability Constant Of the Formed Complex (K Ct )mentioning
confidence: 97%
“…It is involved in processes of energy storage and utilization and therefore plays a vital role in biological reactions [13]. Some of these reactions are considered as simple models for biochemical processes [14].…”
Section: Introductionmentioning
confidence: 99%